Exclusive Breastfeeding Related to Diarrhea Occurrence in Babies Aged 0-6 Months Old at Sudiang Community Health Center, Makassar - Balqis Dwiyanti Haedar; Rauly Ramadhani; Andi Sitti Rahma (HM Publisher, 2022)
Exclusive breastfeeding is a condition in which infants are only given breast milk without the addition of other fluids and foods. until the baby reaches 6 months old. Breast milk strengthen the immune system in infants so they can avoid various diseases including diarrhea. This study aims to determine the relationship between exclusive breastfeeding and the incidence of diarrhea in infants aged 0-6 months in the Sudiang Community Health Center. This research is an analytical survey research with a cross-sectional design. This research was conducted at the Sudiang Health Center, Makassar City in the period November 1st to December 31st, 2019. The total respondents were 89 mothers with babies aged 0-6 months. The results showed that most of the respondents were mothers with male babies (61%), most of the mothers' education was high school graduates (46%), housewives (75%) with low economic background (56%). Exclusive breastfeeding related to the incidence of diarrhea in children aged 0-6 months in the Sudiang Community Health Center with a value of p <0.05 (p = 0.001). In addition, no significant relationship on maternal nipple hygiene to diarrhea in children aged 0-6 months p <0.05 (p = 0.075). In conclusion, this study showed there is a relationship between exclusive breastfeeding and the incidence of diarrhea in children aged 0-6 months in Sudiang Health Center. There is a relationship between hand hygiene and the incidence of diarrhea in children aged 0-6 months in Sudiang Health Center, Makassar.